ANALISA PERAN AUDIT INTERNAL DALAM MENGATASI KECURANGAN TERHADAP LAPORAN KEUANGAN - Rachma, Ade Marselina; Sapitri, Sarah; Novelina, Fransisca (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
Many companies experience fraud in their financial reports. This fraud is caused by many things, such as embezzlement of company assets, falsification of financial reports, etc. The method used is descriptive qualitative which aims to explain the situation in depth, especially in its original context. The data sources used are secondary data sources originating from scientific journals and library studies which are still closely related to the role of audit in overcoming fraud. The role of internal audit is really needed by companies to prevent fraud within the company. This prevention effort should not be considered trivial because it will have an impact on the company's survival in the future. If the role of internal audit is good and good, then fraud will be detected earlier